2018
DOI: 10.2147/cmar.s170526
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TINCR is associated with clinical progression and serves as tumor suppressive role in prostate cancer

Abstract: IntroductionTerminal differentiation-induced non-coding RNA (TINCR) has been suggested to have aberrant expression in multiple human cancers, and functions as tumor suppressor or promoter in various types of human tumors depending on the specific cancer types. The expression status and biological function of TINCR in prostate cancer is still unknown.Materials and methodsIn our study, we detected TINCR expression in prostate cancer tissue samples and cell lines, and analyzed the association between TINCR expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are a class of non-protein-coding RNAs that control gene expression in complex ways (8,9). Numerous studies have revealed that the ectopic expression of lncRNAs is implicated in human cancer (10)(11)(12)(13). As a member of the lncRNA family, the cancer susceptibility candidate 9 (CASC9) gene, located on chromosome 8q21.11, was originally observed to be upregulated in esophageal squamous cell carcinoma (ESCC) (14).…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a class of non-protein-coding RNAs that control gene expression in complex ways (8,9). Numerous studies have revealed that the ectopic expression of lncRNAs is implicated in human cancer (10)(11)(12)(13). As a member of the lncRNA family, the cancer susceptibility candidate 9 (CASC9) gene, located on chromosome 8q21.11, was originally observed to be upregulated in esophageal squamous cell carcinoma (ESCC) (14).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another lncRNA BRE-AS1 has been determined to be downregulated in PCa, and BRE-AS1 overexpression inhibits cell progression and enhances apoptosis of PCa cells [23]. In addition, evidence also demonstrates that lncRNA TINCR is poorly expressed in PCa cells and overexpression of TINCR suppresses cell invasion and migration as well as decreases proliferation in PCa [24]. The results were measurement data and expressed as mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a number of lncRNAs have recently identified that their role in the carcinogenesis process depends on the tissue where they are expressed. Among these lncRNAs is the terminal differentiation-induced non-coding RNA (TINCR) [ [4] , [5] , [6] , [7] ]. This lncRNA has a 3733 nt length and its expression has been recognized at a late phase of human epidermal differentiation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%